17.7k views
1 vote
I desperately need help with this one as well omg.. and i think it also needs a quadratic formula

I desperately need help with this one as well omg.. and i think it also needs a quadratic-example-1

1 Answer

3 votes

Hello,


Formula:\ y=k*a^x+b\\\\ \lim_(x \to -\infty) y=-3 \Longrightarrow -3=k*a^(-\infty)+b=0+b \Longrightarrow b=-3\\\\if \ x=0\ then\ y=-2 \Longrightarrow -2=k*a^0-3 \Longrightarrow k=1\\\\if \ x=1\ then\ y=3 \Longrightarrow 3=a^1-3 \Longrightarrow a=6\\\\\boxed{y=6^x-3}\\

User Daniel Mann
by
5.2k points